Jaminan Sertifikat Hak Milik Atas Tanah Bukan Oleh Pemegang Hak Milik Dalam Perjanjian Kredit Perbankan - Sitania, Aryantho Dwiputra; Pesulima, Theresia Louize; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2021)
Introduction: An agreement is made in oral or written form, where both parties bind themselves and cause legal consequences. The legal protection of the certificate holder can be realized if the issuance of the certificate does not have a juridical defect, namely defects in procedure, substance, or authority. Purposes of the Research: The purpose of this research is to study and find out how the form of legal protection for the first party as the owner of the certificate and find out how the second party's civil liability for certificates borrowed and used as collateral.Methods of the Research: The method used is a normative juridical research method using a statutory approach, a conceptual approach and also a case approach.Results of the Research: The results of this study explain that regarding legal protection for certificate owners whose certificates are used by other people to enter into credit agreements in banking, because the party making the credit agreement does not have a certificate to be used as collateral in the process of borrowing money at the bank, as well as the responsibility of the certificate borrower. in accordance with applicable regulations.